Studi Kritis atas Kepercayaan Orang Manggarai – Flores tentang Komunikasi antara Arwah dengan Orang-orang Hidup - Bernardus Raho; Dr. Alexander Jebadu; Kletus Hekong, Drs.,Lic. (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2023)
This article aims to investigate the communication between the ghosts of the dead and the living. It is quite commonthat the living talk to the ghosts of the dead through different rituals in the tradional religions. On the contrary, the studyabout communication between the ghost of the dead with the living is not very common. Therefore, a question in thisresearch is: “Is there any experience that the ghost of the dead talks to the living?” The assumption is that: there iscommunication between the ghost of the dead and the living. Using descriptive-qualitative method of research, the result ofthis study shows that there is communication between the ghosts of the dead and the living. The communication takes placethrough the medium of the paranormal in which the paranormal man or woman invites the ghost of the dead to talk to his orher family through paranormal man or woman or simply to get the message from the ghost. The communication also takesplace through dreams, and later on the message or messages that iare delivered in the dream become real or reallyhappened. Then, the communication of the ghost of the dead and the living is analyzed using postmodernism, fenomenology,and ethnometodology perspectives. Each perspective argues that the communication between the dead and the living isunderstandable and academically acceptable.Keywords: communication, dead, living, dream, paranormal, post modernism, fenomenolgy, and ethnomethodology.